Chapter 1 Student voices on social exclusion in general primary schools - de Leeuw, R.R (Taylor & Francis, 2019)
Advocates of inclusive education argue that the social inclusion of students with special educational needs (SEN) increases when they are educated with typically developing peers. However, research indicates that this is not apparent for all students with SEN. Students with social, emotional and behavioural diffi culties (SEBD) are often socially excluded. To understand the situation of these students, their voices should be heard. The aim of the current explorative study was to gain insight into: (1) the experiences of students with SEBD regarding victimisation and social exclusion, and (2) the approaches they applied and preferred resolving social problems. We conducted semi-structured interviews with 28 socially excluded students from grades 5 and 6, attending general ( N = 6) and segregated special ( N = 21) primary education. The participants were prompted to talk about their own experiences using hypothetical scenarios. The interviews were analysed using a multi-grounded theory approach. The results show that students preferred diff erent approaches to resolving these social problems than the applied approaches. They would have liked to have seen their peers and teachers to show more initiative. In line with these results, the need to listen to the students' voices are emphasised.